Dealing with jokes in the ESL class: a pedagogical proposal centred on comprehension - Cruz, Manuel Padilla (Letrônica, 2019)
This paper makes a pedagogical proposal to delve into jokes in the ESL classroom and sensitise learners to their complexity. It consists of five instructional phases and is based, on the one hand, on another proposal to teach the pragmatics of speech acts in an L2. On the other hand, this proposal relies on a relevance-theoretic classification of jokes made on the basis of the various linguistic, cultural and cognitive factors that humorists exploit in their production. Since it only centres on how different types of jokes can be distinguished and what their correct comprehension involves, it has a cognitive orientation and does not address issues connected with joke production. The proposal is devised for ESL students with an advanced level of English and ultimately seeks to develop their metalinguistic, meta-cultural and metacognitive abilities as a way of enabling them to grasp the humorousness of funny texts, appraise them and react to them in an appropriate way. ***Lidando com piadas na aula de ESL: uma proposta pedagógica centrada na compreensão*** Este artigo traz uma proposta pedagógica para aprofundar as piadas na sala de aula de ESL (Inglês como língua estrangeira, na tradução para a língua portuguesa) e sensibilizar os alunos a respeito de sua complexidade. Ela consiste em cinco fases instrucionais que, por um lado, baseia-se em outra proposta de ensino da pragmática dos atos de fala em uma L2 e, por outro lado, baseia-se em uma classificação teórica da relevância das piadas feitas com base nos vários fatores linguísticos, culturais e cognitivos que os humoristas exploram em sua produção. Como a proposta se concentra apenas em como os diferentes tipos de piadas podem ser distinguidos e em qual a correta compreensão envolvida, ela tem uma orientação cognitiva e não aborda questões relacionadas à produção da piada. A proposta é elaborada para estudantes de ESL com um nível avançado de inglês e, por conseguinte, busca desenvolver suas habilidades metalinguísticas, meta-culturais e metacognitivas como uma maneira de permitir-lhes compreender o humor de textos engraçados, avaliá-los e reagir a eles apropriadamente.